Inserting Single‐Atom Zn by Tannic Acid Confinement To Regulate the Selectivity of Pd Nanocatalysts for Hydrogenation Reactions. Issue 10 (22nd December 2022) - Zhang, Sha‐Sha; Yi, Jun; Cao, Tai; Guan, Jian‐Ping; Sun, Jia‐Qiang; Zhao, Qin‐Ying; Qiu, Ya‐Jun; Ye, Chen‐Liang; Xiong, Yu; Meng, Ge; Chen, Wei; Lin, Zhou; et al.
Abstract: Precisely controlling the selectivity of nanocatalysts has always been a hot topic in heterogeneous catalysis but remains difficult owing to their complex and inhomogeneous catalytic sites. Herein, an effective strategy to regulate the chemoselectivity of Pd nanocatalysts for selective hydrogenation reactions by inserting single‐atom Zn into Pd nanoparticles is reported. Taking advantage of the tannic acid coating‐confinement strategy, small‐sized Pd nanoparticles with inserted single‐atom Zn are obtained on the O‐doped carbon‐coated alumina. Compared with the pure Pd nanocatalyst, the Pd nanocatalyst with single‐atom Zn insertion exhibits prominent selectivity for the hydrogenation of p ‐iodonitrobenzene to afford the hydrodeiodination product instead of nitro hydrogenation ones. Further computational studies reveal that the single‐atom Zn on Pd nanoparticles strengthens the adsorption of the nitro group to avoid its reduction and increases the d‐band center of Pd atoms to facilitate the reduction of the iodo group, which leads to enhanced selectivity. This work provides new guidelines to tune the selectivity of nanocatalysts with guest single‐atom sites. Abstract : This work reports that inserting Zn single atoms into Pd nanoparticles via a tannic acid coating‐confinement strategy can effectively tune the selectivity of Pd nanocatalyst for the hydrogenation of the iodo group rather than the nitro group in multifunctional compounds, which provides new insights for the rational design of better‐performing nanocatalysts through introducing guest single‐atom metal sites.